2015
DOI: 10.1038/cdd.2015.134
|View full text |Cite|
|
Sign up to set email alerts
|

The NAD+ salvage pathway modulates cancer cell viability via p73

Abstract: The involvement of the nicotinamide adenine dinucleotide (NAD + ) salvage pathway in cancer cell survival is poorly understood. Here we show that the NAD + salvage pathway modulates cancer cell survival through the rarely mutated tumour suppressor p73. Our data show that pharmacological inhibition or knockdown of nicotinamide phosphoribosyltransferase (NAMPT), a rate-limiting enzyme in the NAD + salvage pathway, enhances autophagy and decreases survival of cancer cells in a p53-independent manner. Such NAMPT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 38 publications
4
48
0
Order By: Relevance
“…Grozio et al reported that NMN can reverse Nampt inhibition induced tumor cell death [63]. Sharif et al reported Nampt inhibition enhances autophagy and breast cancer cell death, however, this effect can be effectively reversed by NMN [64]. In this study, we treated NP cells with NMN or rNampt with or without APO866, and we found that both NMN and rNampt can inhibit the cell autophagy induced by APO866.…”
Section: Discussionmentioning
confidence: 85%
“…Grozio et al reported that NMN can reverse Nampt inhibition induced tumor cell death [63]. Sharif et al reported Nampt inhibition enhances autophagy and breast cancer cell death, however, this effect can be effectively reversed by NMN [64]. In this study, we treated NP cells with NMN or rNampt with or without APO866, and we found that both NMN and rNampt can inhibit the cell autophagy induced by APO866.…”
Section: Discussionmentioning
confidence: 85%
“…More potent PARP1 inhibitors, such as PJ34, DPQ, and the marketed drugs olaparib and rucaparib sensitize tumors to DNA damage, although the drugs have limited use because of toxicity (Alano et al, 2010; Almeida et al, 2017; Mathews and Berk, 2008). Inhibitors of NAMPT, such as FK866 and KPT-9274, selectively kills cancer cells, and are currently being tested for efficacy in patients with solid malignancies (Chini et al, 2014; Poljsak, 2016; Sharif et al, 2016). Inhibition of indoleamine 2,3-dioxygenase (IDO), which mediates the first step in the conversion of tryptophan in de novo NAD + synthesis, shows promise in mice as an antitumor therapeutic target (Friberg et al, 2002; Muller et al, 2005; Uyttenhove et al, 2003).…”
Section: Effects Of Nad+ Boosters On Physiology and Health In Mouse Mmentioning
confidence: 99%
“…Metabolic regulation by p53 family appears a key function for their cancer-related but also ageing-related phenotype. All the three members promote mitochondrial respiration thought regulation of different metabolic enzymes, including the glutaminase 2 (Gls2) (Adamovich et al, 2014;Amelio et al, 2014b;Bellomaria et al, 2010Bellomaria et al, , 2012Giacobbe et al, 2013;He et al, 2013;Hu et al, 2010;Sharif et al, 2015;Simon et al, 2014;Velletri et al, 2013;Viticchie et al, 2015). Gls2 regulates glutamine utilization, supplying anaplerotic flux of substrates resulting in promotion of mitochondrial activity and ATP synthesis (Amelio et al, 2014a;Maniam et al, 2015).…”
Section: Oxygen Tension Hypoxia Inducible Factors and Ageing Relatedmentioning
confidence: 99%